1997
DOI: 10.1002/anie.199702881
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Resolution of Racemic Secondary Alcohols by RuII‐Catalyzed Hydrogen Transfer

Abstract: COMMUNICATIONS 243 K. 4282 Reflections were independent and unique, and 2162 with I > 3 OOa(1) (28,,, = 55") were used for the structure solution. The hydrogen atoms at NI and at Ru could be localized and were refined isotropically, and the remaining hydrogen atoms were calculated from ideal geometries. fixed, and included in thecalculation ofthe structural factor. R = 0.050, Rw = 0.067, w' = (o'(E) +0.0025F2)-'. Rigaku AFC7R diffractometer (graphite monochromator, MoK.). The structures were solved with PATTY… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
130
1
3

Year Published

1998
1998
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 356 publications
(136 citation statements)
references
References 61 publications
2
130
1
3
Order By: Relevance
“…Recently Noyori et al reported that efficient kinetic resolution of racemic alcohols could be achieved by hydrogen transfer catalyzed by a diamine ± Ru II complex, [70] and Jacobsen et al described the kinetic resolution of racemic, terminal epoxides by means of a hydrolysis catalyzed by chiral (salen) ± cobalt complexes, which afforded both the unreacted substrates and the products (1,2-diols) in high enantiomeric excess. [71] …”
Section: Miscellaneous Applicationsmentioning
confidence: 99%
“…Recently Noyori et al reported that efficient kinetic resolution of racemic alcohols could be achieved by hydrogen transfer catalyzed by a diamine ± Ru II complex, [70] and Jacobsen et al described the kinetic resolution of racemic, terminal epoxides by means of a hydrolysis catalyzed by chiral (salen) ± cobalt complexes, which afforded both the unreacted substrates and the products (1,2-diols) in high enantiomeric excess. [71] …”
Section: Miscellaneous Applicationsmentioning
confidence: 99%
“…An oxidative variant has also been described. [146] The heterogeneous asymmetric hydrogenation of Blaser and Studer, [147] which provides a precursor for ACE inhibitors, was operated on a ton scale at Ciba-Geigy. A cinchona-doped platinum catalyst was used for the hydrogenation of the ketoester 173 to the 4-phenylhydroxybutyrate 174 (Scheme 68).…”
Section: Asymmetric Hydrogenation Of Ketonesmentioning
confidence: 99%
“…We investigated the oxidation of a series of secondary alcohols into ketones by transfer hydrogenation using acetone as the hydrogen acceptor and in the absence of base, unlike most other catalytic systems (Scheme 3). [7] Reactions were performed at 50 8C in resealable NMR tubes under argon using 2 mol % of catalyst 1 and 5 equivalents of acetone. The reaction progress was followed by 1 H NMR spectroscopy for 12 hours.…”
mentioning
confidence: 99%